2020
DOI: 10.1152/ajpheart.00026.2020
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular adaptations to particle inhalation exposure: molecular mechanisms of the toxicology

Abstract: Ambient air, occupational settings, and the use and distribution of consumer products all serve as conduits for toxicant exposure through inhalation. While the pulmonary system remains a primary target following inhalation exposure, cardiovascular implications are exceptionally culpable for increased morbidity and mortality. The epidemiological evidence for cardiovascular dysfunction resulting from acute or chronic inhalation exposure to particulate matter has been well documented, but the mechanisms driving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 180 publications
(255 reference statements)
0
6
0
Order By: Relevance
“…The application of broad-scale sequencing and “omics” approaches have been used in studies examining the health effects of air toxicants [ 25 27 ]. Specifically, transcriptomics provides a useful tool to determine the immediate adaptation, or maladaptation, after a stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…The application of broad-scale sequencing and “omics” approaches have been used in studies examining the health effects of air toxicants [ 25 27 ]. Specifically, transcriptomics provides a useful tool to determine the immediate adaptation, or maladaptation, after a stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…8). This exposure paradigm has previously demonstrated fetal growth restriction and impaired fetal coronary health www.nature.com/scientificreports/ after gestational exposure 22,24,36,38,39 . For this study we elected to leave dams and litters untouched for one week to prevent maternal rejection of the fetus.…”
Section: Methodsmentioning
confidence: 99%
“…Inhalational exposures to PM2.5 and PM0.1 affect virtually all aspects of cellular functions systemically and in multiple different organs. Human and experimental animal studies showed that PM2.5 and PM0.1 elicited immune, inflammatory, oxidative, and endoplasmic reticulum stress and affected carcinogenic [45], metabolic, and epigenetic pathways [44].…”
Section: Particulate Mattermentioning
confidence: 99%